#### Answer

$(f\circ g\circ h)(x)=-3x+13$

#### Work Step by Step

We are given $f(x)=x+1$, $g(x)=3x$, and $h(x)=4-x$.
So $(f\circ g\circ h)(x)=f(g(h(x)))=f(g(4-x))=f(3(4-x))=3(4-x)+1\\=12-3x+1=-3x+13$.

Published by
Pearson

ISBN 10:
0-32187-896-5

ISBN 13:
978-0-32187-896-0

$(f\circ g\circ h)(x)=-3x+13$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.